0\\\\\Big (\sqrt{\frac{1}{4y^2}-1}-\frac{1}{2y}\Big )\cdot \Big (\frac{\sqrt{1+2y}}{\sqrt{1+2y}-\sqrt{1-2y}}+\frac{1-2y}{\sqrt{1-4y^2}+2y-1}\Big )=\\\\=\Big (\sqrt{\frac{1-4y^2}{4y^2}}-\frac{1}{2y}\Big )\cdot \Big (\frac{\sqrt{1+2y}}{\sqrt{1+2y}-\sqrt{1-2y}}}+\frac{1-2y}{\sqrt{(1-2y)(1+2y)}-(\sqrt{1-2y})^2}\Big )=\\\\" alt="\; \; y>0\\\\\Big (\sqrt{\frac{1}{4y^2}-1}-\frac{1}{2y}\Big )\cdot \Big (\frac{\sqrt{1+2y}}{\sqrt{1+2y}-\sqrt{1-2y}}+\frac{1-2y}{\sqrt{1-4y^2}+2y-1}\Big )=\\\\=\Big (\sqrt{\frac{1-4y^2}{4y^2}}-\frac{1}{2y}\Big )\cdot \Big (\frac{\sqrt{1+2y}}{\sqrt{1+2y}-\sqrt{1-2y}}}+\frac{1-2y}{\sqrt{(1-2y)(1+2y)}-(\sqrt{1-2y})^2}\Big )=\\\\" align="absmiddle" class="latex-formula">